Pengaruh Campuran Air-Nanopartikel CuO sebagai Coolant dan Laju Aliran terhadap Parameter Perpindahan Kalor pada Radiator (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2021)
The aim of this study was to determine the effect of volume fraction and fluid flow ratetowards the heat transfer parameters in the Honda Vario radiator cooling system. This study was conducted by using a test equipment which a radiator used as main cooling system. The inlet fluid temperature is constantly kept in accordance with the engine working temperature. Temperature measurements were carried out on variations in flowrate and fluid concentration using a digital thermometer.Variations used in fluid volume fraction are 0%, 0.1%, 0.3%, and 0.5%. While, the variation of the fluid is 12 lpm, 18 lpm, and 24 lpmmeasuredby a flowmeter. The highest change in the value of the heat transfer coefficient was found in the large volume fraction and flow rate. However, at higher volume fractions, the Reynlods number will tend to decrease. To get a better rate of heat transfer and cooling, a higher volume fraction and fluid flow is used. As for the flow variation, it usually adjusts to the vehicle user. The use of nanofluids will helpto reduce the heat in the radiator cooling system.